Photoinduced radical tandem annulation of 1,7-diynes: an approach for divergent assembly of functionalized quinolin-2(1H)-ones - Chen, Daixiang; Song, Zhi-Jie; Yan, Shenghu; Li, Guigen; Wang, Jia-Yin; Zhang, Yue (Frontiers in Chemistry, 2024)
The first photocatalytic trichloromethyl radical-triggered annulative reactions of amide-linked 1,7diynes with polyhalomethanes were established for the flexible assembly of functionalized quinolin-2(1H)-ones with generally acceptable yields. With the installation of the aryl group (R 1 ) into the alkynyl moiety, C-center radical-initiated Kharasch-type addition/nucleophilic substitution/elimination cascade to produce quinolin-2(1H)-ones-incorporating gem-dihaloalkene, whereas three examples of polyhalogenated quinolin-2(1H)-ones were afforded when amide-linked 1,7-diynes bearing two terminal alkyne units were subjected with BrCX3 by exploiting dry acetonitrile as solvents.